Meaning Surplus in Contemporary Iraqi Sculpture (Al-Academy, 2018)
The present research is concerned with studying the appearance and essence of meaning in contemporary sculpture by addressing the problematic how to flow of meaning its multiplicity and the flow of its surplus, resulting from the transformations of the artistic form and the variety of its methods which results to a new and different strategies in circulation and aesthetic reception to achieve this task, we have relied on models of modern Iraq sculpture, which fit in its form and raw materials with the concept of phenomenon studied. Therefore, the research topic were divided into four axes:- the first axe included an introduction about the subject. The introduction included the problems of research and its importance, aim represented by highlighting on the subject of surplus meaning and mechanisms to achieve in contemporary Iraqi sculpture. The second axis only included the theoretical framework, which specialized to review the concept of meaning and methods of its formation and the most important intellectual references affecting the artistic process. The third axis included the applied procedures of how to determine the community and sample, methodology and tools used in the analysis of samples. the fourth and final axis to show the results reached by the study, which was the most important is the excess of meaning is related to the imaginary embodiment of the structure and of the form, this is what happens when the sculptural work leaves the realistic simulation to be based on new methods such as abstraction, reduction, partial and total in the appearance of the sculptural output